2016
DOI: 10.1194/jlr.m065888
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid enhances macrophage autophagy and attenuates atherogenesis

Abstract: This article is available online at http://www.jlr.org recycled for downstream metabolism (1). Among the three major kinds of autophagy, macroautophagy, microautophagy, and chaperone-mediated autophagy, macroautophagy is the most prevalent form and, thus, commonly referred to as autophagy (2, 3). Over the past decade, research efforts regarding this ancient biological process have been revived due to the realization that alterations in autophagy play crucial pathological roles in many diseases (4, 5) for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Several observations have demonstrated that autophagy facilitates intracellular lipid droplet degradation and cholesterol efflux to impede foam cell formation [30,31]. Thus, current experimental evidence supports a role for autophagy-mediated efflux that favors ABCA1 expression [32,33]. These observations are consistent with the possibility that autophagy plays a major role in the expression of ABCA1.…”
Section: Discussionsupporting
confidence: 79%
“…Several observations have demonstrated that autophagy facilitates intracellular lipid droplet degradation and cholesterol efflux to impede foam cell formation [30,31]. Thus, current experimental evidence supports a role for autophagy-mediated efflux that favors ABCA1 expression [32,33]. These observations are consistent with the possibility that autophagy plays a major role in the expression of ABCA1.…”
Section: Discussionsupporting
confidence: 79%
“…Autophagy is induced by UA in various cells. UA has been demonstrated to promote macrophage autophagy and thereby suppresses IL‐1β secretion, promotes cholesterol efflux and attenuates atherosclerosis in mice . UA also activates autophagy and, hence, has been shown to induce cytotoxicity and reduce tumor growth in the cervical cancer cell line TC‐1 in a concentration‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…UA has been demonstrated to promote macrophage autophagy and thereby suppresses IL-1β secretion, promotes cholesterol efflux and attenuates atherosclerosis in mice. [25] UA also activates autophagy and, hence, has been shown to induce cytotoxicity and reduce tumor growth in the cervical cancer cell line TC-1 in a concentration-dependent manner. [19] In the present study, we first demonstrated that UA induced HSFB autophagy in a dose-and timedependent manner (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…other steroidal sapogenins, namely sarsapogenin and protodioscin, detected in fenugreek possessed significant anticancer, hypocholesterolemic, and antidepressant activities [6][7][8][9][10][11][12], exhibited the beneficial effects on the cardiovascular system [10], and might take a part in the regulation of glycemia and high blood pressure [8][9]13]. Besides, oleanolic and ursolic acids are known for different biological activities, their ability to reduce blood pressure, to regulate cholesterol level, and to induce the apoptosis of cancer cells [14][15][16][17][18][19][20]. Interestingly, ursolic acid represents one of the most important constituents of fenugreek seed.…”
mentioning
confidence: 99%
“…Interestingly, ursolic acid represents one of the most important constituents of fenugreek seed. In the literature so far, it was reported to be present only in its ethanol-aqueous extract [16][17][18][19][20][21][22]. The concurrent presence of oleanolic acid and ursolic acid, its isomer, in plant material might be responsible for their possible synergistic effect on several health impairments [23][24][25].…”
mentioning
confidence: 99%